Evaluation of cardiac MRI and ambulatory blood pressure monitoring in a pediatric Turner syndrome population. (March 2019) - Tahhan, Nabil; Mura, Thibault; Jeandel, Claire; Guillaumont, Sophie; De La Villeon, Gregoire; Vincenti, Marie; Soulatges, Camille; Matecki, Stefan; Amedro, Pascal
Abstract: Background: The benefits of cardiac MRI in the diagnosis of cardiac abnormalities in adults with Turner syndrome (TS) have been shown by several studies. High blood pressure frequently occurs in TS patients; therefore ambulatory blood pressure monitoring (ABPM) is routinely performed in adults with TS. However, potential benefits of either technique remain undetermined in the pediatric TS population. Aims: To evaluate the potential benefits of cardiac MRI and ABPM in pediatric patients with TS. Methods: A total of 19 girls with TS, aged between 9 and 18 years old, were prospectively included in a cross-sectional study from May 2015 to November 2015. We evaluated data from both cardiac MRI and ABPM by comparison with 2D echocardiography and instant measurement of blood pressure. Results: Of the 16 cardiac MRI performed, 4 (25%) revealed anatomical abnormalities undiagnosed by echocardiography. Our analysis demonstrated a low correlation between echocardiography and cardiac MRI in measuring diameters of the aortic root. ABPM revealed 5 cases (29.5%) of moderate hypertension, 4 of which were previously unknown. Conclusions: This study has shown an advantage of using cardiac MRI and ABPM for diagnosing cardiovascular abnormalities in pediatric TS patients, therefore we recommend the routine use of both examinations to improve overall care and ensure a better transition into adulthood. Highlights: High blood pressure affects almost 50% of adult turner syndrome patients, although the age of onset is not fully understood. The benefits of cardiac MRI in the adult population of Turner syndrome have been demonstrated. In the pediatric Turner syndrome population, the benefit of ABPM and cardiac MRI has not yet been studied. This study has shown an advantage of using cardiac MRI and ABPM in pediatric Turner syndrome patients. We recommend the routine use of both examinations to improve overall care and ensure a better transition into adulthood.